Biomass Stove Design Based Quality Function Deployment (QFD) and Design For Manufacture And Assembly (DFMA) - Yohanes Yohanes; Muhammad Idris (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
This study aims to design a biomass stove as a solution for lack of LPG gas in the community in Batu Panjang, Rupat Island, Riau. The Quality Function Deployment (QFD) method is used in this study by elaborating consumer needs through public opinion needs (questionnaire survey) and elaboration of the characteristics of consumer needs. A House of Quality (HoQ) matrix was created to determine the technical characteristics for design analysis of biomass stove and designed using the Design for Manufacture and Assembly (DFMA). The result was a development of